History of Thought and History of Humankind in Plato’s Protagoras - Corradi, Michele (Peitho. Examina Antiqua, 2024)
In Plato’s Protagoras, prompted by Socrates, Protagoras grapples with the complex problem of the nature of the sophistike techne that he professes. To clarify the nature of his teaching, he reconstructs a history of his discipline, identifying a series of figures who preceded him, concealing their own activities under the guise of other technai. Furthermore, through the famous myth of Prometheus, he places the sphere in which he operates, the politike, at the center of the development of human communities. In response to Protagoras, Socrates, through a curious reinterpretation of the past, identifies Spartan brachylogy and the activities of the Seven Sages as precursors to his own philosophy. As is also evident from the comparison with the Ancient Medicine, in the Protagoras, Plato, not without a hint of irony, seems to stage the fifth century intellectuals’ attempt to define their activity through a skillful reworking of human history.